Green Tea Polyphenols Upregulate the Nrf2 Signaling Pathway and Suppress Oxidative Stress and Inflammation Markers in D-Galactose-Induced Liver Aging in Mice - Wang, Dongxu; Wang, Taotao; Li, Zhanming; Guo, Yuanxin; Granato, Daniel (Frontiers in Nutrition, 2022)
The beneficial effects of green tea polyphenols (GTPs) on D-galactose (D-Gal)-induced liver aging in male Kunming mice were investigated. For this purpose, forty adult male Kunming mice were divided into four groups. All animals, except for the normal control and GTPs control, were intraperitoneally injected with D-Gal (300 mg/kg/day for 5 days a week) for twelve consecutive weeks, and the D-Gal-treated mice were allowed free access to 0.05% GTPs (w/w) diet or normal diet for twelve consecutive weeks. Results showed that GTPs administration improved the liver index and decreased transaminases and total bilirubin levels. Furthermore, GTPs significantly increased hepatic glutathione and total antioxidant levels, and the activities of superoxide dismutase, catalase, and glutathione S-transferase (GST). Furthermore, GTPs downregulated 8-hydroxy-2-deoxyguanosine, advanced glycation end products, and hepatic oxidative stress markers, such as malondialdehyde and nitric oxide. Additionally, GTPs abrogated dysregulation in hepatic Kelch-like ECH-associated protein 1 and nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream target gene expression (heme oxygenase 1, NAD(P)H:quinone oxidoreductase 1, and GST) and inhibited tumor necrosis factor-α, transforming growth factor-β, and interleukin (IL)-1β and IL-6 in the liver of treated mice. Finally, GTPs effectively attenuated D-Gal-induced edema, vacuole formation and inflammatory cell infiltration. In conclusion, GTPs showed antioxidant and anti-inflammatory properties in D-Gal induced mice, and may be considered a natural alternative to the effects of hepatic aging.